Who Constitutes Un/Authorized Co-Owners? Staff's Privacy Management at an Anti-Violence Nonprofit. Issue 4 (8th August 2022) - Biss, Danielle C.; Dykstra-DeVette, Tiffany A.
ABSTRACT: People with intellectual and developmental disabilities (IDDs) experience higher rates of sexual violence and face unique challenges as they disclose their traumatic experiences to nonprofit organizations. Although there is little empirical research, it is important that nonprofit staff understand how to negotiate the privacy of clients who are living with IDDs. Drawing on 12-months of ethnographic data, this study investigates communication challenges that staff experienced as they managed the privacy of their clients with IDDs. Guided by Communication Privacy Management theory, interpretations reveal three challenges that staff experience: 1) difficulties identifying private information ownership, 2) conceptualizing private information control, and 3) managing turbulence. The study concludes with theoretical and practical implications for privacy management and nonprofits serving clients with IDDs.